Clinical outcome and prognostic factors of patients with Richter syndrome: real‐world study of the Spanish Chronic Lymphocytic Leukemia Study Group (GELLC). (9th June 2020) - Abrisqueta, Pau; Delgado, Julio; Alcoceba, Miguel; Oliveira, Ana Carla; Loscertales, Javier; Hernández‐Rivas, Jose A.; Ferrà, Christelle; Cordoba, Raul; Yáñez, Lucrecia; Medina, Angeles; Motlló, Cristina; Iacoboni, Gloria; et al.
Summary: Richter syndrome (RS) is an uncommon evolution of chronic lymphocytic leukaemia (CLL) with a dismal prognosis. Clinical‐biological features predicting outcome and best therapeutic approach for these patients remain to be established. In this study, 128 patients with RS, including 112 diffuse large B‐cell lymphoma (DLBCL)‐type RS, 15 Hodgkin lymphoma (HL)‐type RS, and one plasmablastic lymphoma, were identified in 11 centres of the Spanish CLL Study Group (GELLC). The median overall survival (OS) was 5·9 months for DLBCL‐type RS and 30·8 months for HL‐type RS. Eastern Cooperative Oncology Group Performance Status, haemoglobin level, platelet count, serum lactate dehydrogenase and β2‐microglobulin levels, tumour protein p53 ( TP53 ) abnormalities in the CLL clone concomitant to RS, number of prior therapies, and clonal relationship between CLL and RS, were associated with OS in patients with DLBCL‐type RS. A platelet count of <100 × 10 9 /l, prior CLL therapy (0 vs. ≥1), and presence of TP53 alterations maintained an independent prognostic impact in the multivariate analysis. Patients without any of these factors had a better clinical outcome, with a median OS of 75·3 months, while patients with one or two or more of these factors presented a median OS of 25·5 and 3 months, respectively. Although OS of patients with RS is generally poor, a proportion of patients achieved prolonged survival. Treatment of RS remains a medical need, and further therapeutic approaches with novel therapies are warranted.